OPTIMIZATION OF VILLAGE ASSET MANAGEMENT IN INCREASING VILLAGE ORIGINAL INCOME IN SUKA MAJU VILLAGE - Nirwan Saleh; Ikram Muhammad; Ely Ibrahim (LP2M Universitas Bina Mandiri Gorontalo, 2024)
The purpose of this study is to analyze the optimization of asset management in increasing the original income of villages in Sukamaju Village. The method used in this study is a qualitative method with a descriptive approach which is carried out for 3 months from July to September 2023 since the writing of the research design. Data collection through observation, interviews and documentation to the head of Sukamaju village, village secretary, general office and subsequent administration of the people of Sukamaju Village. Furthermore, the data is managed and analyzed qualitatively. The results showed that asset management in the original improvement of Sukamaju Village has been optimal from the procurement aspect because it has been in accordance with self-management and third parties in accordance with applicable regulations. However, it has not been optimal in terms of planning, utilization and maintenance due to incomplete asset data, the absence of regulations on the commercialization of village assets, concurrent managers and lack of asset management competence.